ATR represents a therapeutic vulnerability in clear cell renal cell carcinoma - Philipp Seidel; Anne Rubarth; Kyra Zodel; Asin Peighambari; Felix Neumann; Yannick Federkiel; Hsin Huang; Rouven Hoefflin; Mojca Adlesic; Christian Witt; David J. Hoffmann; Patrick Metzger; et al. (JCI Insight, 2022)
Metastatic clear cell renal cell carcinomas (ccRCCs) are resistant to DNA-damaging chemotherapies, limiting therapeutic options for patients whose tumors are resistant to tyrosine kinase inhibitors and/or immune checkpoint therapies. Here we show that mouse and human ccRCCs were frequently characterized by high levels of endogenous DNA damage and that cultured ccRCC cells exhibited intact cellular responses to chemotherapy-induced DNA damage. We identify that pharmacological inhibition of the DNA damage–sensing kinase ataxia telangiectasia and Rad3-related protein (ATR) with the orally administered, potent, and selective drug M4344 (gartisertib) induced antiproliferative effects in ccRCC cells. This effect was due to replication stress and accumulation of DNA damage in S phase. In some cells, DNA damage persisted into subsequent G2/M and G1 phases, leading to the frequent accumulation of micronuclei. Daily single-agent treatment with M4344 inhibited the growth of ccRCC xenograft tumors. M4344 synergized with chemotherapeutic drugs including cisplatin and carboplatin and the poly(ADP-ribose) polymerase inhibitor olaparib in mouse and human ccRCC cells. Weekly M4344 plus cisplatin treatment showed therapeutic synergy in ccRCC xenografts and was efficacious in an autochthonous mouse ccRCC model. These studies identify ATR inhibition as a potential novel therapeutic option for ccRCC.